STRATEGI KOMUNIKASI PEMASARAN PASTA GIGI TERHADAP PENERIMAAN KONSUMEN (STUDI KASUS PASTA GIGI ENZIM TANPA DETERJEN DAN CARA KERING) - Novrian Novrian (Universitas Mercu Buana, 2018)
Marketing a product that has typical takes effort to promote in order to be accepted in the market such as toothpaste. The right strategy in market communication makes it easier for products to be accepted as the product it has a characteristic unique as a formof more value compared with the product in general. Through the integrated Marketing Communication for introducing the product has superiority that still unknown by consumers it is excepted to create the patterns of communication the effective and efficient for company in marketing their products.With the qualitative deskritif through the approach the case can be found the concept Integrated Marketing Communication that is dominant and effective in introducing products with a particular trait, to support the accuracy of the research it have to do an interview with the employees of various divisions the related to promotion activities from company. The experience of the company in the dissemination of information.The results showed that the implementation integreted marketing communication it has an important role in communication marketing ttothpaste enzim to customers.The conclusion of the analysis of the implementation of the communicatons marketing toothpaste was found the approach of education in the program integrated marketing communication for the products can be accepted by consumers.Keywords: Integrated Marketing Communication, Komunikasi Pemasaran, Strategi, Edukasi